Assessing the stability of co-digesting sewage sludge with pig manure under different mixing ratios. (1st August 2020) - Xu, Suyun; Wang, Chongyang; Sun, Yangyang; Luo, Liwen; Wong, Jonathan Woon-Chung
Graphical abstract: Highlights: Maximum methane yield was found in co-digester of TS 6%. Excess PM leads to the accumulation of VFAs and ammonia. More balanced C/N ratio is obtained in the co-digestion. Methane yield is negatively correlated with F/I, TAN, FAN and VFA/TIC. Abstract: This study assessed the digester stability and overall methane production of co-digestion of sewage sludge (SS) and pig manure (PM). Four different ratios of PM were mixed with SS to reach different final concentrations of total solids (TS), i.e. 4%, 6%, 8% and 10%. Volatile solids (VS) reduction rate decreased along with an increase in TS%, and the maximum cumulative methane yield of 342 mL/g VSrem was obtained in treatment with TS of 6%. When TS was ≥ 8%, accumulation of volatile fatty acids (VFAs), free ammonium nitrogen (FAN) and total ammonium nitrogen (TAN) were observed. At a TS content of 10%, VFAs accumulated to > 20000 mg/L and the highest FAN was 481 mg/L. The suppression of methanogenesis was negatively correlated with FAN and VFA/TIC (P < 0.05). Co-digestion demonstrated to be an effective way to improve the methane yield from SS due to the enriched biodegradable organic substance and more balanced C/N ratio by incorporating PM.